Interval prolongation of etanercept in rheumatoid arthritis, ankylosing spondylitis, and psoriatic arthritis: a randomized controlled trial. (4th March 2023) - Ruwaard, J; L' Ami, MJ; Kneepkens, EL; Krieckaert, CLM; Nurmohamed, MT; Hooijberg, F; van Kuijk, AWR; van Denderen, JC; Burgemeister, L; Rispens, T; Boers, M; Wolbink, GJ
Abstract : Objective: The majority of patients with a rheumatic disease treated with etanercept may be overexposed. Data regarding etanercept tapering are scarce, particularly in psoriatic arthritis (PsA) and ankylosing spondylitis (AS). We compared extending the dose interval to continuation of the standard dose and studied the success rate of etanercept discontinuation. Etanercept concentrations were measured throughout the study. Method: 160 patients with rheumatoid arthritis (RA), PsA, or AS with sustained minimal disease activity (MDA) were enrolled in this 18-month, open-label, randomized controlled trial. The intervention group doubled the dosing interval at baseline and discontinued etanercept 6 months later. The control group continued the standard dose for 6 months and doubled the dosing-interval thereafter. The primary outcome was the proportion of patients maintaining MDA at 6 month follow-up. Results: At 6 months, MDA status was maintained in 47 patients (63%) in the intervention group and 56 (74%) in the control group (p = 0.15), with comparable results in all rheumatic diseases. And median etanercept concentrations decreased from 1.50 µg/mL (interquartile range 1.06– 2.65) to 0.46 µg/mL (0.28–0.92). In total, 40% discontinued etanercept successfully with maintained MDA for at least 6 months. Conclusion: Etanercept tapering can be done without losing efficacy in RA, PsA, and AS patients in sustained MDA. A substantial proportion of patients could stop etanercept for at least 6 months. In many patients, low drug concentrations proved sufficient to control disease activity. However, the risk of minor and major flares is substantial, even in patients continuing standard dosing.